The Enforcement of Law and Policy on STM with the Emergence of Advanced Technologies - Elham Farahani; Shouping Li (Advanced Space Law)
Space Traffic Management (STM) using advanced technologies is effective for the safety and sustainability of outer space by improving Space Situational Awareness (SSA), data sharing information system, collision avoidance, and space debris mitigation methods. Nevertheless, developing an effective STM using advanced technologies without considering an effective legal and regulatory framework can pose some difficulties in terms of monitoring and enforcement. This paper presents the relevance of innovative advanced technologies and STM, focusing on the enforcement of law and policy. It highlights an urgent need to update the legal framework to ensure their practicality amidst the widespread use of advanced technologies in space activities. It also examines the fact that the utilization of advanced technologies in the environment of outer space presents both opportunities and challenges, especially with the emergence of Artificial Intelligence (AI) and Machine Learning (ML). Although revising all regulations is anticipated to be a challenging and time-consuming process, it can be implemented through communication and cooperation between spacefaring countries, private space operators, and other relevant entities at the national and international levels, as well as permanent monitoring and evaluation of all technologies to ensure that they are used in a manner that is consistent with established laws and policies.